2022
DOI: 10.3390/polym14214522
|View full text |Cite
|
Sign up to set email alerts
|

The Preliminary Assessment of New Biomaterials Necessitates a Comparison of Direct and Indirect Cytotoxicity Methodological Approaches

Abstract: Background: Cytotoxicity testing is a primary method to establish the safety of biomaterials, e.g., biocomposites. Biomaterials involve a wide range of medical materials, which are usually solid materials and are used in bone regeneration, cardiology, or dermatology. Current advancements in science and technology provide several standard cytotoxicity testing methods that are sufficiently sensitive to detect various levels of cellular toxicity, i.e., from low to high. The aim was to compare the direct and indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…The results suggested NR/BioS (90/10) and the neat NR as the best candidates to be used in vivo, as both specimens presented higher cell proliferation. Chraniuk et al 72 observed similar behavior in their study of the preliminary assessment of new biomaterials, which necessitates a comparison between direct and indirect cytotoxicity methodologies. A biological study was conducted on chitosan‐BG composites loaded with different bioglasses (P5, P5Sr2, P5Zn2) at a ratio of 1:0.5; 1:1; 1:2 72 .…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The results suggested NR/BioS (90/10) and the neat NR as the best candidates to be used in vivo, as both specimens presented higher cell proliferation. Chraniuk et al 72 observed similar behavior in their study of the preliminary assessment of new biomaterials, which necessitates a comparison between direct and indirect cytotoxicity methodologies. A biological study was conducted on chitosan‐BG composites loaded with different bioglasses (P5, P5Sr2, P5Zn2) at a ratio of 1:0.5; 1:1; 1:2 72 .…”
Section: Resultsmentioning
confidence: 96%
“…Chraniuk et al 72 observed similar behavior in their study of the preliminary assessment of new biomaterials, which necessitates a comparison between direct and indirect cytotoxicity methodologies. A biological study was conducted on chitosan‐BG composites loaded with different bioglasses (P5, P5Sr2, P5Zn2) at a ratio of 1:0.5; 1:1; 1:2 72 . Proliferation results obtained after incubation with extracts (the indirect method) and composites (the direct method) indicated statistically significant differences between the test methods for each composite, as observed in the authors' comparison study.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations